Subtract 3x − 4y − 7z from the sum of


Subtract 3x − 4y − 7z from the sum of x − 3y + 2z and − 4x + 9y − 11z.


Let first add the expressions $x-3 y+2 z$ and $-4 x+9 y-11 z$. We get:

$(x-3 y+2 z)+(-4 x+9 y-11 z)$

$=x-3 y+2 z-4 x+9 y-11 z$

$=x-4 x-3 y+9 y+2 z-11 z$            (Combining like terms)

$=-3 x+6 y-9 z$             (Combining like terms)

Now, subtracting the expression $3 x-4 y-7 z$ from the above sum; we get:

$(-3 x+6 y-9 z)-(3 x-4 y-7 z)$

$=-3 x+6 y-9 z-3 x+4 y+7 z$

$=-3 x-3 x+6 y+4 y-9 z+7 z$              (Combining like terms)

$=-6 x+10 y-2 z$                       (Combining like terms)

Thus, the answer is $-6 x+10 y-2 z$.


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now